Total Ionization Cross Sections due to Electron Impact of Ammonia from Threshold to 10 MeV - Pramod Kumar; Amrita; Yogesh Kumar; Lalit Kumar; Kiran Pal (International Journal of Engineering and Management Research, 2022)
In the present paper, we have employed modified Khare-BEB method [Atoms, (2019)] to evaluate total ionization cross sections by the electron impact for ammonia in energy range from the ionization threshold to 10 MeV. The theoretical ionization cross sections have been compared to the available previous theoretical and experimental results. The collision parameters dipole matrix squared and CRP also have been calculated. The present calculations were found in remarkable agreement with the available experimental results.